The spatial distribution of haze over the Bojanala District - Barnes, Beverley Cindy (My University, 2016)
The air quality over the Bojanala District has been identified as an area of concern. The Bojanala Platinum District falls within the Waterberg Priority Area, which was declared as a priority area for air quality in 2012. This study was conducted in the southern part of the Bojanala district to identify the spatial and temporal distribution of aerosols over the district. Aerosol optical thickness and Ångstrom exponent were derived using data retrieved from direct solar radiation measurements using hazemeters during winter 2008, early winter 2009 and late winter 2010. Results of the study reveal that aerosol loadings differ significantly as winter progresses. AOT levels are found to be considerably higher during winter and late winter, compared with the early winter campaign. Diurnal variation during the late winter campaign is found to be very similar to that of the early winter campaign, with little variation in aerosol loadings and characteristics during the day; while the winter 2008 campaign reveals a significant decreasing trend in AOT and Ångstrom exponent as the day progresses. The AOT and Ångstrom exponent levels for the different campaigns, local sources and the diurnal trends identified assist in the attribution of domestic fuel burning practices; and the concentration of pollutants emitted in the area by inversion layers to the characteristics of the aerosol loadings during winter. The high AOT and contribution of fine mode particles during late winter is attributed to the onset of the biomass burning season. The importance of industrial sources to the aerosol loadings is clear during all three campaigns; however, it is clear that aerosols at different levels in the atmosphere have a significant impact on AOT over the district. The vertical distribution of aerosols is explored through the use of trajectories and associated surface wind roses which indicate that foreign airmasses from the Mpumalanga Highveld and the Atlantic Ocean clearly have a significant impact on the aerosol loadings over the Bojanala District and are associated with extremes in AOT levels. Further, spatial analysis reveals that the highest concentrations of aerosols (associated with larger particles) are identified toward the eastern side of the district except during late winter. It is probable that the aerosols in the Bojanala District may have a significant regional climatic impact which requires further investigation.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2015.
Keywords: Air quality.; Air--Pollution.; South Africa--North West--Bojanala Platinum District.